Narrative Networks: Patterns of Technology and Organization - Pentland, Brian T.; Feldman, Martha S. (Organization Science, 2007)
This paper introduces the narrative network as a device for representing patterns of “technology in use.” The narrative network offers a novel conceptual vocabulary for the description of information and communication technologies (ICTs) and their relationship to organizational forms. We argue that as ICTs have become increasingly modular and recombinable, so have organizational processes and forms. The narrative network draws on concepts from structuration theory, actor network theory (ANT), and the theory of organizational routines. A narrative network expresses the set of stories (performances) that have been, or could be, generated by combining and recombining fragments of technology in use. This paper discusses how thinking of technology and organizations as narrative networks influences our understanding of design.